"Customary International Law: A Third World Perspective": Reflections in Light of an Approach to CIL Based on Fundamental Ethical Principles. (13th November 2018) - Lepard, Brian D.
Abstract : B.S. Chimni's stimulating article makes an important contribution to the burgeoning literature on customary international law (CIL) by examining CIL from the perspective of developing states, a perspective underrepresented in this literature. His article articulates well many valid points about the sociohistorical biases of CIL. At the same time, there may be reasons for more optimism than Chimni appears to possess about the ability of CIL to serve global interests, including those of the Third World. Furthermore, some of Chimni's proposals merit further refinement. In this essay I propose to evaluate the strengths and potential shortcomings of Chimni's arguments in light of an approach to CIL that I have developed that is based on fundamental ethical principles recognized in international law. After laying out an alternative theory that still has many resonances with Chimni's proposals, I discuss critically three of the key theses articulated by Chimni: First, that CIL is inherently colonialist and inconsistent with the values of Third World peoples; second, that even contemporary customary international human rights law (IHRL) is a means of furthering global capitalism to the detriment of Third World peoples; and third, that the remedy for CIL's biases lies in the creation of a "postmodern" doctrine of CIL that incorporates reference to the "juridical conscience of humankind."